Evolusi cara berpikir manusia: Kontribusi pemikiran Auguste Comte dan C.A. Van Peursen - Apriliyani, Sanra Melisya; Barokah, Rakan; Clarisyah, Amanda Ayu; Faisol, Faisol (Maliki Interdisciplinary Journal, 2025)
This paper explores the evolution of human thought through the philosophical perspectives of two prominent figures: Auguste Comte and C.A. Van Peursen. Comte’s Law of Three Stages theological, metaphysical, and positive emphasizes scientific methods as the pinnacle of human understanding. Conversely, Van Peursen focuses on cultural dynamics in the development of human consciousness through mythical, ontological, and functional stages. Although their approaches differ, both thinkers highlight the gradual progression of human thinking. Comte underscores objectivity and scientific rationality, while Van Peursen stresses the interconnection between science, technology, and human values. This study recommends an interdisciplinary approach that integrates scientific logic with ethical and cultural dimensions in the development of knowledge. Hence, science can advance without losing its humanistic essence.